(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2024)
Wound closure is one of the important steps of surgical dressing and suturing is the most commonly used method of wound closure. The process of suturing takes very long time for surgery and increases the patient’s risk of anesthesia awareness. Skin glues are a safe and effective method to close selected wounds. They are also cost-effective and help prevent infection. Ideally, wounds should be less than 4 cm, not contaminated or infected and have skin edges that are not under tension. Wounds should be closed within 12 hours. Novel methods of wound closure have been introduced to address these issues, most notably cyanoacrylate tissue glues. The evidence would suggest that the use of cyanoacrylate tissue glue is associated with a reduction in closure time and costs. On a daily basis, dermasurgeons are facing different kinds of wounds that have to be closed. With a plethora of skin closure materials currently available, choosing a solution that combines excellent and rapid cosmetic results with practicality and cost-effectiveness is preferred.